Hinterland setting and composition of an Oligocene deep rift-lake sequence, Gulf of Tonkin, Vietnam: Implications for petroleum source rock deposition. (January 2020) - Rizzi, M.; Fyhn, M.B.W.; Schovsbo, N.H.; Korte, C.; Hovikoski, J.; Olivarius, M.; Thomsen, T.B.; Keulen, N.; Thuy, N.T.T.; Hoang, B.H.; Dung, B.V.; Toan, D.M.; et al.
Abstract: Most SE Asian oil accumulations are sourced from Paleogene lacustrine mudstones. Even so, the mechanisms controlling formation of these source rocks are not fully understood. Bach Long Vi Island, located in the northwestern South China Sea, offers a unique opportunity to study these mechanisms. A continuous, 800 m thick, organic rich and highly oil-prone, lacustrine section was investigated in outcrop and in a continuously cored section. The Oligocene deep-lake succession formed in the Bach Long Vi Graben that connects the Beibuwan Basin with the Yinggehai-Song Hong Basin. Petrography, detrital zircon U-Th-Pb geochronology and heavy mineral assemblages of sandstone intervals document a locally derived sediment source isolated from the Red River. Orientations of ripple cross lamination in gravity flow sands indicate axial sediment transport along the graben. Combined with the local structural configuration, this suggests that sediments were derived from the Qixi High through a relay ramp located about 10 km south of the island. Rare earth and major elements, detrital zircon ages, sandstone petrography and garnet composition, suggest a dominantly Ordovician – Silurian aged felsic and metasedimentary hinterland. The limited sediment supply from the small hinterland allowed tectonic subsidence to keep pace with graben infill. This promoted the establishment of a long-lived, deep lake favorable for source rock generation. In addition, heavy mineral and geochemical data document an unusually high content of detrital phosphate minerals in the investigated section indicative of a phosphate-rich hinterland. Tropical leaching resulted in an extraordinary high phosphorus input into the lake that catalyzed a high organic productivity and promoted the generation of highly prolific, oil-prone source rocks. The study documents that hinterland size and composition play a primary role in lacustrine source rock deposition. Comparable petroleum source rocks are likely to exist in other ancient rift basins surrounded by small, phosphate-rich hinterlands sheltered from significant sediment input. Highlights: Provenance of the sediment was local and stable through time. No influence from the Red or Pearl rivers was identified. Sediments were derived through a relay ramp located at the eastern rift shoulder. Hinterland was composed by Ordovician – Silurian aged felsic rocks and metasediments. Hinterland size and composition played a primary role in source rock development.